Pirating Pirates of the Caribbean: The Curse of Cyberspace - Phau, Ian; Teah, Min; Lwin, Michael (Routledge, 2013)
This study investigates the factors influencing the ‘illegal’ downloading of films and TV series through P2P networks. Specifically, it examines how social and ethical orientations and attitudes towards downloading impact on downloading intentions. The neutralisation theory and theory of planned behaviour are used to underpin the research framework. The data analysis of 284 usable responses produced several significant relationships. Facilitating conditions, social factors, collectivism, and personal moral obligation were found to predict attitudes towards ‘illegal’ downloading. Social factors, collectivism, personal moral obligation, and attitudes towards ‘illegal’ downloading were also found to influence intentions to download. The findings derived from this study will provide marketers and policy makers with strategic and managerial initiatives to counteract this persistent problem.